PENGARUH KARAKTERISTIK ORGANISASI DAN KARAKTERISTIK INDIVIDU TERHADAP PENGEMBANGAN KARIR PEGAWAI PADA KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI SULAWESI TENGAH - Susandra, Vebbie Leentje (Katalogis, 2013)
This research aimed at finding out the factors influencing career development within the Ministry of Religion of Central Sulawesi Province and in particular at analyzing the influence of organization characteristic which include : organization resources, organization climate and organization structure toward the officer career development, and individual characteristic which cover: skill, education, work experience toward the officer career development, as well as at analyzing both characteristic simultaneously toward the officer career development within the Ministry of Religion of Central Sulawesi Province. The research used quantitative analysis technique using all the officers within the Ministry of Religion of Central Sulawesi Province totaling 127 respondents, and employed stratified random sampling technique using Slovin formula, having 56 respondents. To analize the hypotheis, multiple linear regression method employing SPSS 17 program was used. It is found that the organization characteristic (organization resources, organization climate and organization structure) had positive and significant influence toward the officer career development whereas the individual characteristic had positive influence but not significant toward the officer career development.